Living on the slope. The Middle and Upper Paleolithic occupation of Feldberg “Steinacker” Leben auf dem Hang. Die mittel- und jungpaläolithische Besiedlung von Feldberg „Steinacker” - Bradtmöller, Marcel; Bubenzer, Olaf; Hecht, Stefan; Tschocke, Diethard; Calvo, Aitor; Fernández, Arantzazu Jindriska Pérez; Schmidt, Christoph; Marreiros, Joao; Henselowsky, Felix; Hattermann, Merlin-Janis; Bauer, Lisa; El-Kassem, Marcel (Hugo Obermaier-Society for Quaternary Research and Archaeology of the Stone Age, 2022)
This article is dedicated to the Paleolithic open-air site of Feldberg “Steinacker”, located between the Rhine and the Black Forest near Freiburg/Breisgau in South-West Germany. The site was discovered by W. Mähling in 1969 and is primarily known for the presence of tanged points (Font-Robert type), as well as a possible connection via raw material transport to the cave sites of the Swabian Jura. However, stratigraphic context, site formation processes and site function remained unclear. In 2018, the Heritage Management of Baden-Wuerttemberg and the University of Rostock began the first scientific investigations at the site. It was possible to document a knapping area from the Gravettian, presumably in situ. The excavations also revealed a Middle Paleolithic occupation, making “Steinacker” for the moment the only open-air site in South-West Germany where a stratification of Middle to Upper Paleolithic is present. The investigations were accompanied by additional analyses related to site-formation processes and artefact morphology. Geomagnetic and geoelectric prospection as well as sedimentological drilling revealed a complex paleo-relief that was very different from the current topography. Micromorphology and optically stimulated luminescence dating confirmed that the excavated archaeological stratigraphy was largely intact. Moreover, use-wear analysis showed that pieces with strong indications of frost alterations were possibly used on a regular basis at the site.
CRIS-Team Scopus Importer:2024-12-16
Keywords: ERT Survey; Geomagnetic Survey; Gravettian; Mousterian; open-air site; site-formation processes; use-wear analysis